Beyond borders: exploring the impact of augmented reality on intercultural competence and L2 learning motivation in EFL learners - Liu, Song; Gao, Shengbing; Ji, Xiaoyan (Frontiers in Psychology, 2023)
This mixed-methods study explores the impact of augmented reality (AR) on the development of intercultural competence and L2 learning motivation among Chinese EFL learners. Forty-eight intermediate-level learners were randomly assigned to an experimental group receiving ARbased language instruction or a control group receiving traditional instruction. Pre-and post-tests were administered to both groups to assess their intercultural competence and L2 learning motivation. The experimental group utilized an AR application, exposing learners to diverse cultural scenarios, customs, and norms. Findings indicate that the experimental group exhibited significantly higher levels of intercultural competence and L2 learning motivation compared to the control group. Qualitative data further revealed that AR-based instruction enhanced learners' engagement, motivation, and cultural understanding. This study underscores the potential of AR in fostering intercultural competence development and L2 learning motivation within the EFL context.